2020
DOI: 10.1080/14623943.2020.1821631
|View full text |Cite
|
Sign up to set email alerts
|

Transformative learning and the hidden dynamics of transformation

Abstract: Transformative learning is 'an approach to teaching based on promoting change, where educators challenge learners to critically question and assess the integrity of their deeply held assumptions about how they relate to the world around them'. While it seems to be clear what is subject to change (assumptions), apparently it is less obvious how we can (critically) reflect on assumptions, especially since most of them operate outside of our awareness. The question that follows is: How can we bring these hidden a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Prior studies have demonstrated that schooling is rooted in White logics, and the sociohistorical context significantly impacts the academic achievement of Black boys [58,63,64]. Our study aligns with the work of these scholars, emphasizing that racial equity must be addressed at the organizational, school, and district levels, and leaders must comprehend the embeddedness of White logics and the necessity for disruption.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Prior studies have demonstrated that schooling is rooted in White logics, and the sociohistorical context significantly impacts the academic achievement of Black boys [58,63,64]. Our study aligns with the work of these scholars, emphasizing that racial equity must be addressed at the organizational, school, and district levels, and leaders must comprehend the embeddedness of White logics and the necessity for disruption.…”
Section: Discussionsupporting
confidence: 83%
“…These findings potentially lead to recurring barriers to change and issues that undermine the change processes and spur transformation [58]. Also, we found leaders raised contradictions that were central aspects of their leadership, such as buy-in and fostering a safe space for teachers, accountability measures, and conflating equality with equity.…”
Section: Resultsmentioning
confidence: 85%
“…Jack Mezirow—the founder of transformative learning (TL) theory, claims TL facilitates adult learners’ learning through generating individual stories and evaluating their past beliefs and experiences (Mezirow, 1997a ). Mezirow and many scholars believe that reflective practice is the core of TL (Anand et al, 2020a , 2020b ; Cho & Johnson, 2020 ; Daniëls et al, 2020 ; Eschenbacher, 2020 ; Eschenbacher & Fleming, 2020 ). Through reflection, one can acquire insights about oneself (Anand et al, 2020a ; Welch et al, 2020 ).…”
Section: A Review Of Literature and Conceptual Frameworkmentioning
confidence: 99%
“…A series of reflective practices lead to the alignment of actions that can further refine people’s mental habits and points of view (Mezirow, 1996 , 1997b , 2003 ). Reflective discourse allows participants to make space for new understandings of themselves and others, which helps them to identify skills and strengths in an appreciative environment (Eschenbacher, 2020 ). Mezirow ( 1998 ) agrees with Taylor ( 1994 ) that reflective discourses enable participants to gain a critical awareness of assumptions and transform them to become more open, integrative, and inclusive.…”
Section: A Review Of Literature and Conceptual Frameworkmentioning
confidence: 99%
“…It is important to apply transformative learning, especially to students who have only received learning using traditional models. Transformative learning can promote change with an approach that challenges students to be more critical of the surrounding environment (Eschenbacher, 2020).…”
mentioning
confidence: 99%